DAMPAK INTELLECTUAL CAPITAL TERHADAP NILAI PASAR PERUSAHAAN DENGAN RETURN ON ASSET SEBAGAI VARIABEL INTERVENING - Dennis Sutandar; Prima Apriwenni (Universitas Bunda Mulia, 2018)
Nowadays, intellectual capital become a very valuable asset on business. Intellectual Capital is an intangible asset that can create value added and competitive advatage for the company. The value added and competitive advatage will increase investors trust that can cause the raising value of the firm. Intellectual capital was measured by Vallue Added Intellectual Capital that consist of human capital, structural capital, and customer capital. The increasing profit was measured by return on asset (ROA). ROA indicates the company abilities to generate earnings (profitability). The firm value was measured by Tobin’s Q. The population in this research using a manufacturing company, especially infrastructure, utility, and transportation listed in Indonesia Stock Exchange during the period 2013-2015. Based on purposive sampling method, 19 samples were obtained, so there are 57 of observation data. The analysis techniques use are multiple linear regresion and path analysis. The result of this research showed that: (1) Intellectual capital has a positive and significant influence toward return on assets. (2) Intellectual capital has a positive and significant influence toward firm value. (3) Return on assets has a positive and significant influance on firm value. (4) Intellectual capital has a positive and significant influence toward firm value through return on assets. Keyword : Intellectual Capital, Return on Asset, Firm Value, Tobin’s Q